Optimalisasi Lingkungan Lembaga Dakwah Menghadapi Era Disrupsi: Pendekatan Inovasi dan Kewirausahaan - Irfan Syuhudi; Cecep Castrawijaya (Himada: Jurnal Mahasiswa Dakwah dan Komunikasi, 2024)
The era of disruption is characterised by rapid and significant changes in various sectors, including technological, economic, and social. These changes require da'wah institutions to innovate and adapt to remain relevant in meeting the needs of the people and a dynamic society. This research discusses the optimisation of the environment of da'wah institutions in facing the era of disruption through innovation and entrepreneurship approaches. In the context of rapid social and technological change, da'wah institutions are required to adapt to remain relevant and effective in delivering religious messages. The method used in this research is a literature study with a qualitative approach, where data is collected from various sources such as journals, scientific articles, and books. The analysis focused on the ability of da'wah institutions to innovate, create sharia-based entrepreneurship programmes, and use digital technology to expand the reach of da'wah. By applying this approach, da'wah institutions can overcome emerging challenges and capitalise on existing opportunities, so as to strengthen their role in an increasingly complex society. The results of this study are expected to provide practical recommendations for da'wah organisations to improve their capacity in facing disruption.